Familial polyposis coli syndromes - Drews, Michał; Banasiewicz, Tomasz; Krokowicz, Piotr; Pławski, Andrzej; Paszkowski, Jacek (Contemporary Oncology/Współczesna Onkologia, 2006)
Familial polyposis coli syndromes are caused by germline mutation in the APC gene. Multiple adenomatous polyps, early age of malignant transformation and high frequency of extracolonic manifestations are the main clinical symptoms of polyposis syndromes. Detection of polyposis syndromes is done by pedigree analysis, genetic examination and/or endoscopical examination of the large bowel. The APC gene is screened for mutations by the use of heteroduplex and SSCP methods. Endoscopy of the large bowel is necessary in case of undetected mutations and for decision about surgery of carriers of the mutation. Resection of the large bowel is the only indicated procedure. Restorative proctocolectomy is the most common, but colectomy and laparoscopic procedures are described more and more frequently.